A STUDY OF DRUG RELATED PROBLEMS IN CHRONIC KIDNEY DISEASE PATIENTS IN HOSPITAL - Sholihah, Inayatush; Salindri Pratama, Tiara Dewi; Ikakusumawati, Novita Dhewi; Rahardjoputro, Rolando (Jurnal Farmasi Sains dan Praktis, 2024)
Patients with chronic kidney disease experience decreased kidney function (as an organ of elimination) and receive various drugs, so they are susceptible to Drug Related Problems (DRP). This study aimed to identify the type of potential DRP and analyzed the influence of gender, age, number of drugs, co-morbidities and length of stay on the incidence of DRP in hospitalized chronic kidney disease patients. This study was a cross-sectional study with retrospective data collection. The subjects of the study were chronic kidney disease patients who underwent hospitalization at a hospital in Surakarta at 2016-2021. The incidence of DRP was analyzed descriptively using the PCNE V9.1 algorithm, while the associations between risk factors and the incidence of DRP was analyzed statistically using the Fisher’s Exact Test. Data were obtained from 54 patients whose progress was followed up through medical record. The results showed that 36 patients (66.67%) had DRP while 18 patients (33.33%) did not. In the Problem category there were 22 events while in the Cause category there were 34 events. The results of statistical analysis using the Fisher's Exact Test showed that there were no significant associations between the risk factors (gender, age, number of drugs, number of co-morbidities, length of stay) and the incidence of DRP in hospitalized chronic kidney disease patients.